Reforming Corporate Governance : Experiences with Public Takeover Bids in Chile and Panama - Clarke de la Cerda, Alvaro (International Finance Corporation, Washington, DC, 2014)
Focus 6 covers the experiences of two high-profile cases in Chile and Panama and analyzes reforms that shape new legislation and protect minority shareholders. The first article in this publication explores the impact the reforms to the regulation of corporate governance in 2000 on the capital market in Chile. After seven years of implementing the new law it is possible to consider, with a more informed vision, what the positive and negative elements that strengthening the regulation of corporate governance have brought. The experience of Panama is also an ironic commentary on the Chilean experience. It is the case for reform to protect minority shareholders which was introduced by the Panamanian securities regulator. In reaction to this, some interested individuals rejected the reform proposal in theory, tying up the initiative in the courts, but accepted it and followed it in practice. And continue to do so even today. The history, regulation and the practice of takeovers in Panama presents interesting paradoxical and contradictory features, which can provide lessons that can be of general use.